Evolution of the structure of the 41+ states in Po isotopes. (May 2020) - Stoyanova, M.; Karayonchev, V.; Rainovski, G.; Jolie, J.; Pietralla, N.; Blazhev, A.; Dewald, A.; Djongolov, M.; Esmaylzadeh, A.; Fransen, C.; Garbe, J.; Gerhard, L.; et al.
Abstract: The lifetime of the 4 1 + state in 208 Po has been measured using γ − γ fast-timing technique with LaBr3 (Ce) Detectors. The experiment was performed at the FN Tandem facility at the University of Cologne. The preliminary results are discussed in the scope of the systematic behavior of the transition strengths between yrast states in polonium isotopes.